(untitled) (Current Horticulture, 2024)
The frontline demonstration on okra was conducted on 70 ha during 2016, 2017, 2018 and 2019 at farmers fields in tribal area of Dungarpur district of Rajasthan. A total of 350 demonstrations were conducted on 350 farmers fields with package of practices. The average yield was obtained 145.9, 147.5, 148.6 and 150.2 q/ha under demonstrated practice, whereas in farmers practice it was 102.2, 103.1, 102.6 and 103.4q/ha yield during summer season of 2016, 2017, 2018 and 2019, respectively. An average on technology gap of four years frontline demonstration programme was 3.95qha. The per cent increase in yield with high-yielding over local variety was 42.76 to 45.26 per cent. The extension gap recorded was 43.7, 44.4, 46.0 and 46.8 q/ha during all years. An average technology index was 2.60 per cent during all the four years, showing the efficacy of technical interventions. The demonstrated practice also gave higher gross return, net return with higher benefit: cost ratio compared to farmers practice.